Analysis of submerged implant towards mastication load using 3D finite element method (FEM) - Ritonga, Widia Hafsyah Sumarlina; Rusjanti, Janti; Rusminah, Nunung; Miranda, Aldilla; Dirgantara, Tatacipta (Padjadjaran Journal of Dentistry, 2016)
Introduction: The surgical procedure of dental implant comprising one stage surgery for the non-submerged implant design and two stages for submerged. Submerged design is frequently used in Faculty of Dentistry Padjadjaran University as it is safer in achieving osseointegration. This study has been carried out to evaluate resistant capacity of an implant component design submerged against failure based on location and the value of internal stress during the application of mastication force using the 3D Finite Element Method (FEM). Methods: The present study used a CBCT radiograph of the mandibular patient and Micro CT Scan of one submerged implant. Radiograph image was then converted into a digital model of 3D computerized finite element, subsequently inputted the material properties and boundary condition with 87N occlusion load applied and about 29N for the shear force. Results: The maximum stress was found located at the contact area between the implant and alveolar crest with stress value registered up to 193.31MPa located within an implant body where is understandable that this value is far below allowable strength of titanium alloy of 860 MPa. Conclusion: The location of the maximum stress was located on the contact area between the implant-abutment and alveolar crest. This implant design is acceptable and no failure observed under mastication load.